2020
DOI: 10.1007/s12671-020-01446-y
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Mindfulness-Based Social-Emotional Learning Program CARE for Teachers Within Croatian Context

Abstract: Objectives The initial results of mindfulness-based interventions (MBIs) designed for teachers have shown promise for promoting teachers' social and emotional competencies, their health, and well-being. The present study examined the effectiveness of CARE for Teachers program outside the USA in the country of Croatia, Europe, through self-report assessment and collection of physiological data. Methods The sample included 54 teachers and other school personnel from public schools of which 25 were involved in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 44 publications
(86 reference statements)
1
10
0
1
Order By: Relevance
“…Specifically, we found that Chinese teachers in Hong Kong who attended the 8-week mindfulness training based on .b Foundations showed significantly higher life satisfaction, more positive affect, and better general health, along with lower levels of insomnia, stress, and negative affect than the control group both at immediate post-test and two-month follow-up, with medium to large effect sizes. Our findings aligned with those of prior studies conducted in Western populations (e.g., Beshai et al, 2016 ; Crain et al, 2017 ; Harris et al, 2016 ; Hwang et al, 2019 ; Jennings et al, 2013 , 2017 , 2019 ; Mihic et al, 2020 ; Roeser et al, 2013 ) and indicated that MBI is effective in enhancing teachers’ psychological well-being, reducing their psychological distress, and improving their physical health in WEIRD and non-WEIRD cultures alike (Klingbeil & Renshaw, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Specifically, we found that Chinese teachers in Hong Kong who attended the 8-week mindfulness training based on .b Foundations showed significantly higher life satisfaction, more positive affect, and better general health, along with lower levels of insomnia, stress, and negative affect than the control group both at immediate post-test and two-month follow-up, with medium to large effect sizes. Our findings aligned with those of prior studies conducted in Western populations (e.g., Beshai et al, 2016 ; Crain et al, 2017 ; Harris et al, 2016 ; Hwang et al, 2019 ; Jennings et al, 2013 , 2017 , 2019 ; Mihic et al, 2020 ; Roeser et al, 2013 ) and indicated that MBI is effective in enhancing teachers’ psychological well-being, reducing their psychological distress, and improving their physical health in WEIRD and non-WEIRD cultures alike (Klingbeil & Renshaw, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…Prior studies have examined the moderating effects of teachers’ baseline well-being on the intervention effectiveness of MBI (Jennings et al, 2019 ; Mihic et al, 2020 ). Despite investigating the effects of the same MBI program (i.e., CARE), Jennings et al ( 2019 ) found a significant moderating effect of teachers’ baseline psychological distress on their improvement in emotion regulation in a sample of elementary school teachers in New York, USA, whereas Mihic et al ( 2020 ) did not observe such moderation effect of participants’ well-being among elementary school teachers in Zagreb, Croatia. Our findings among Chinese teachers in Hong Kong corroborate the results obtained by Jennings et al ( 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations